CHARACTERIZATION OF GLULAM SENGON (Paraserianthes falcataria) FROM SAWING INDUSTRIAL WASTE BASED ON TYPE OF ADHESIVE AND PRESS TIME - Cahya Fahmi, Putri
Wood utilization for human needs is increasing day by day. However, the amount of land and the existence of forests and trees as raw material is reduced. Laminated timber from sawn timber waste is one of the alternatives that can overcome these problems. One of the wood species that can be utilized is Jabon (Anthocepalus cadamba). Jabon is a fast growing wood species that can be upgraded through wood lamination to be an alternative raw material for industrial wood production. The adhesives that used in this research are PVAc, UF, and UF + Tannins. The addition of tannins in the UF is expected to be an environmentally friendly adhesive and reduce the negative impact of synthetic adhesives. The purpose of this research was to determine the physical properties (moisture content and specific gravity), mechanical properties (adhesive strength, MOE, and MOR), delamination, and formaldehyde emissions of laminated jabon using PVAc, UF, and UF + Tannins adhesives, and the best pressing time of each adhesives. The tanin used was obtained by extracting surian bark with a yield of 9.43%. The Laminated testing refers to the JAS 234-2003 standard. The results are compared with the JAS 234-2003 standard, SNI 01-5008.2-1999, and SNI 03-3527-1994. The results for moisture content with PVAc adhesive 13.9% (24 hours), UF 15.4% (24 hours), and UF + Tannins 15.6% (48 hours). This result does not qualify the standard of JAS, because in this research, the water content of dry air wood is desired. The results for specific gravity with PVAc 0.452 (24 hours), UF 0.484 (72 hours), and UF + Tannins 0.445 (48 hours). The results for adhesive strength with PVAc adhesive 28,400 kg / cm² (24 hours), UF 63,910 kg / cm² (72 hours), and UF + Tannins 71,682 kg / cm² (72 hours). The results for MOE with PVAc adhesive 32659.26 kg / cm² (72 hours), UF 54127.10 kg / cm² (48 hours), and UF + Tannins 63060.51 kg / cm² (72 hours). The results for MOR with PVAc adhesive 198.28 kg / cm² (72 hours), UF 323.39 kg / cm² (72 hours), and UF + Tannins 383.55 kg / cm² (72 hours). In general, the addition of tannin shows a greater test value than UF without tannin in all laminated tests and the longer pressing time also increases the strength of laminated produced. Variations in the value of the physical and mechanical properties of the test results are due to the lack of sorting of the sample, the unavoidable presence of wood defects, and variations in the moisture content of the initial wood. The results of delamination testing did not pass the JAS 234-2003 standard. This is because the gluing process is less than perfect, which is characterized by several samples that have been opened during the trimming process. All formaldehyde emissions are valued at F ****, which means that all adhesives are classified as the environmentally friendly category. The best pressing time for the PVAc, UF, and UF + Tannin adhesive is 72 hours.